2015
DOI: 10.1016/j.acap.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of ICD Codes: Identifying Physical Abuse in 4 Children's Hospitals

Abstract: Objective To assess the accuracy of International Classification of Diseases, 9th Revision, Clinical Modification (ICD-9-CM), codes in identifying cases of child physical abuse in 4 children’s hospitals. Methods We included all children evaluated by a child abuse pediatrician (CAP) for suspicion of abuse at 4 children’s hospitals from January 1, 2007, to December 31, 2010. Subjects included both patients judged to have injuries from abuse and those judged to have injuries from accidents or to have medical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 13 publications
(21 reference statements)
2
34
0
Order By: Relevance
“…26 A study of 4 children's hospitals demonstrated that abuse ICD-9-CM codes among children with TBI who underwent evaluation by a child abuse pediatrician had a sensitivity of 85.0% and specificity of 92.1% in correctly identifying abused children. 27 The use of ICD-9-CM codes to identify children with AHT at non-children's hospitals and hospitals without abuse specialists, however, has not been validated. Use of ICD-9-CM codes to calculate the incidence of AHT in children less than 1 year of age using nationally weighted administrative data of pediatric admissions (not limited to children's hospitals) produced comparable incidence estimates to those derived from a study using a prospective AHT surveillance strategy of all hospitals in North Carolina.…”
Section: Discussionmentioning
confidence: 99%
“…26 A study of 4 children's hospitals demonstrated that abuse ICD-9-CM codes among children with TBI who underwent evaluation by a child abuse pediatrician had a sensitivity of 85.0% and specificity of 92.1% in correctly identifying abused children. 27 The use of ICD-9-CM codes to identify children with AHT at non-children's hospitals and hospitals without abuse specialists, however, has not been validated. Use of ICD-9-CM codes to calculate the incidence of AHT in children less than 1 year of age using nationally weighted administrative data of pediatric admissions (not limited to children's hospitals) produced comparable incidence estimates to those derived from a study using a prospective AHT surveillance strategy of all hospitals in North Carolina.…”
Section: Discussionmentioning
confidence: 99%
“…We used a previously published coding scheme using validated abuse codes to identify children hospitalized for CPA. 2,20,21 In short, this scheme requires that 1 of the following 4 criteria be met: (1) ICD-9-CM codes for an injury (800-959) and abuse (995.50, 995.54, 995.55, 995.59, or E967), (2) ICD-9-CM codes for an injury and assault (E960, E966, E968), (3) ICD-9-CM codes for retinal hemorrhages (362.81) or anoxic brain injury (348.1) and abuse, or (4) any ICD-9-CM code for shaken infant syndrome (995.55). Exclusion criteria included late-onset injury effects, e-codes indicating that the injury occurred at a location not typical for abuse (eg, farms), or an abuse code at any previous encounter.…”
Section: Study Populationmentioning
confidence: 99%
“…5,22,29,30,32,34 Leventhal et al used ICD-9 E-codes to identify young children with abusive rib fractures, an ascertainment method shown to have high specificity for abuse. 22,35,36 Nonetheless, the abuse diagnosis criteria remain unclear with this method; thus, the study received a rating of 4.…”
Section: Resultsmentioning
confidence: 99%